TLR1/2 and 5 induce elevated cytokine levels from rheumatoid arthritis monocytes independent of ACPA or RF autoantibody status. (28th June 2020) - Thwaites, Ryan S; Unterberger, Sarah; Chamberlain, Giselle; Walker-Bone, Karen; Davies, Kevin A; Sacre, Sandra
Abstract: Objective: RA is an autoimmune inflammatory joint disease. Both RF and ACPA are associated with more progressive disease and higher levels of systemic inflammation. Monocyte activation of toll-like receptors (TLRs) by endogenous ligands is a potential source of increased production of systemic cytokines. RA monocytes have elevated TLRs, some of which are associated with the disease activity score using 28 joints (DAS28). The aim of this study was to measure TLR-induced cytokine production from monocytes, stratified by autoantibody status, to assess if their capacity to induce cytokines is related to autoantibody status or DAS28. Methods: Peripheral blood monocytes isolated from RA patients and healthy controls were stimulated with TLR1/2, TLR2/6, TLR4, TLR5, TLR7, TLR8 and TLR9 ligands for 18 h before measuring IL-6, TNFα and IL-10. Serum was used to confirm the autoantibody status. Cytokine levels were compared with RF, ACPA and DAS28. Results: RA monocytes demonstrated significantly increased IL-6 and TNFα upon TLR1/2 stimulation and IL-6 and IL-10 upon TLR5 activation. TLR7 and TLR9 activation did not induce cytokines and no significant differences were observed between RA and healthy control monocytes upon TLR2/6, TLR4 or TLR8 activation. When stratified by ACPA or RF status there were no correlations between autoantibody status and elevated cytokine levels. However, TLR1/2-induced IL-6 did correlate with DAS28. Conclusions: Elevated TLR-induced cytokines in RA monocytes were not related to ACPA or RF status. However, TLR1/2-induced IL-6 was associated with disease activity.